Hybrid Minimally Invasive Approach for Combined Obstructive Coronary Artery Disease and Severe Aortic Stenosis. Issue 2 (March 2020) - Pirelli, Luigi; Patel, Nirav C.; Scheinerman, Jacob S.; Brinster, Derek R.; Hemli, Jonathan M.; Basman, Craig; Kliger, Chad A.
Objective: There is a high prevalence of concomitant coronary artery disease (CAD) and aortic stenosis (AS), and these conditions can be treated with a variety of invasive and/or percutaneous approaches. The aim of this study is to demonstrate the feasibility, efficacy, and safety of a staged transcatheter aortic valve replacement (TAVR) after a hybrid minimally invasive direct coronary artery bypass surgery (MIDCAB) to treat combined complex CAD and AS. Methods: Six patients with concomitant CAD and severe AS underwent staged treatment of their CAD with MIDCAB and TAVR. All patients had significant complex left main or left anterior descending artery (LAD) stenosis deemed to be not amenable to percutaneous coronary intervention (PCI). Results: The average syntax score was 22±8 and the Society of Thoracic Surgeons score for surgical AVR was 8±3%. All patients underwent a single vessel MIDCAB for revascularization of the LAD (three patients required additional PCI for non-LAD disease). Two patients had pre-TAVR balloon aortic valvuloplasty and one patient also required treatment of severe mitral valve regurgitation with percutaneous edge-to-edge repair (the MitraClip). There was no intraprocedural or hospital mortality. No neurological deficits or vascular complications were recorded. Conclusions: A hybrid staged approach for combined complex CAD and severe AS with MIDCAB, PCI, and TAVR is a valid option in high-risk patients. The order and timing of these procedures must be tailored to the patient's clinical symptoms, stability, and severity of disease.